Enhancement of gravity ventilation in buildings - Nakielska, Magdalena; Pawłowski, Krzysztof (International Conference “Environmental Engineering”, 2017)
Nowadays, people are looking for solutions related to ventilation, cooling or heat demand systems, which would be energy efficient and, at the same time, would not cause the degradation of the surrounding environment. As far as ventilation is concerned, an good solution is a natural ventilation, which improves thermal comfort rooms without increasing the consumption of electrical energy in the building. In order to improve the mode of action of the natural ventilation in the building, one can mount various elements supporting the air flow. One of them is a solar chimney. In order to check the correct operation of a gravity ventilation installation in Poland’s climatic conditions, the measurements was carried out on a test stand on the 3.1 building of UTP University of Science and Technology in Bydgoszcz. The received results show the intensification of the air flow through the room the value between 50% and 150%, depending on a measuring hour (Chen et al. 2003). These research results were compared with the research results received before the installation of the solar chimney on the ducts of the gravity ventilation.